Analisis komparatif self confidence siswa kelas khusus dan kelas reguler - Santoso Santoso; Richma Hidayati (Jurnal Konseling dan Pendidikan, 2021)
The purpose of this study was to compare the self-confidence of students in special classes and regular classes and to know class differences. This study uses a quantitative approach with a comparative design. The research sample consisted of 80 students with 35 regular class students and 45 special class students who were determined using the Proportional Random Sampling Technique. The instrument was adapted from the confidence of the instrument and data analysis used comparational analysis using the Difference Test with the SPSS program. The conclusion of this study is that there are differences in the confidence of students in special classes and regular classes. A total of 30 students in a special class have high self-confidence and 5 students have a sufficient level of self-confidence, while students in regular class, as many as 20 students have sufficient self-confidence and 25 students have less self-confidence. And shows that the difference between special classes and regular classes greatly affects the level of student confidence.